Chapter Quality of life in Health Care: focus on patients - Digrandi, Angela (Proceedings e report, 2023)
In this work, we show a narrative review conserning instruments to measure the quality of Life in Health Care from a patients point of view. In particular, we pay attention on the construction of questionnaire and on the choice of the areas/settings (physical, emotional, social, functional, economical,...).